Manual thinning increases fruit size and sugar content of Citrus reticulata Blanco and affects hormone synthesis and sugar transporter activity - Cong LIU; De-xiong LI; Xian-biao HUANG; Fu-qiong ZHANG; Zong-zhou XIE; Hong-yan ZHANG; Ji-hong LIU (Journal of Integrative Agriculture, 2022)
Manual fruit thinning (MFT) in fruit trees has been previously shown to increase fruit size and enhance fruit quality, but the effect of MFT on Ponkan (Citrus reticulata Blanco) and the underlying mechanisms remain poorly understood. In this study, efforts were made to elucidate how MFT influences the fruit quality of Ponkan. The results showed that MFT substantially increased fruit size and elevated fruit total soluble solids in comparison with the fruit from the unthinned trees (used as control). Expression analyses demonstrated that mRNA abundance of three important sugar transporter genes, including CrSUT1, CrSTP1 and CrTMT1, was evidently elevated in the flesh of thinned fruit when compared with those of the control. In addition, MFT prominently up-regulated the transcript levels of various auxin and gibberellin (GA) biosynthesis and signaling genes, including CrYUC6, CrAUX/IAA, CrGA20ox1 and CrGA3ox1. Concurrently, the contents of endogenous IAA and GA3, measured at 90 d after fruit thinning, were notably elevated in the fruit from trees with the thinning treatment relative to the control, although no difference was detected in the two groups before the thinning manipulation. Taken together, these results indicate that manual fruit thinning could greatly improve fruit quality, which may be attributed to promoting fruit expansion due to the increased auxin levels and expediting sugar accumulation through the up-regulation of sugar transporter genes.